2020
DOI: 10.3389/fonc.2020.559730
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Long Non-coding RNAs and mRNAs in Plasma of Clear Cell Renal Cell Carcinoma Patients Using Microarray and Bioinformatic Analysis

Abstract: Objective: The roles of long non-coding RNAs (lncRNAs) in the diagnosis of clear cell renal cell carcinoma (ccRCC) are still not well-defined. We aimed to identify differentially expressed lncRNAs and mRNAs in plasma of ccRCC patients and health controls systematically.Methods: Expression profile of plasma lncRNAs and mRNAs in ccRCC patients and healthy controls was analyzed based on microarray assay. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway-based approaches were used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Recently, bioinformatic analysis has been generally performed in the identification of biomarkers, which provides insight into the molecular mechanism of disease progression (5)(6)(7)(8)(9). Microarray technology can be used for a wide range of bioinformatic analysis and the development of new computational techniques remains an active area of bioinformatics research that will continue to expand over the coming years (10)(11)(12). Moreover, researches have shown that immune cell infiltration plays an increasingly remarkable role not only in transplantation, but also in various diseases (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bioinformatic analysis has been generally performed in the identification of biomarkers, which provides insight into the molecular mechanism of disease progression (5)(6)(7)(8)(9). Microarray technology can be used for a wide range of bioinformatic analysis and the development of new computational techniques remains an active area of bioinformatics research that will continue to expand over the coming years (10)(11)(12). Moreover, researches have shown that immune cell infiltration plays an increasingly remarkable role not only in transplantation, but also in various diseases (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…We further studied the clinical and molecular characteristics of our target gene in ccRCC and evaluated its potential role in the development and progression of ccRCC. Studies have shown that PLAUR is highly expressed in many tumors, including ccRCC [ 21 , 31 ]. This is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…For the 20 other genes in our prognostic model, there were also some studies to support our conclusions. EPB41L4B was differently expressed in both plasma and neoplastic tissues and was correlated with the OS rate in clear-cell renal cell carcinoma patients [45]. The high expression level of ERRFI1 was associated with radiosensitivity and high OS rates in lung cancer patients [46].…”
Section: Discussionmentioning
confidence: 99%